2018
DOI: 10.1108/jeim-05-2017-0069
|View full text |Cite
|
Sign up to set email alerts
|

G-RAM framework for software risk assessment and mitigation strategies in organisations

Abstract: Purpose Malicious attackers frequently breach information systems by exploiting disclosed software vulnerabilities. Knowledge of these vulnerabilities over time is essential to decide the use of software products by organisations. The purpose of this paper is to propose a novel G-RAM framework for business organisations to assess and mitigate risks arising out of software vulnerabilities. Design/methodology/approach The G-RAM risk assessment module uses GARCH to model vulnerability growth. Using 16-year data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 76 publications
(135 reference statements)
0
13
0
Order By: Relevance
“…Therefore, IT managers need to carefully choose software with uncorrelated vulnerabilities while building system configurations (Chen et al , 2011; Temizkan et al , 2017). Diversification of correlated cyber-risk enables efficient assessment and mitigation of cyber-risks and reduces “software monoculture” (Chen et al , 2011; Temizkan et al , 2017; Biswas and Mukhopadhyay, 2018). Chen et al (2011) have developed a simulation-based study to identify the correlated risks arising due to shared software vulnerabilities across multiple software platforms.…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, IT managers need to carefully choose software with uncorrelated vulnerabilities while building system configurations (Chen et al , 2011; Temizkan et al , 2017). Diversification of correlated cyber-risk enables efficient assessment and mitigation of cyber-risks and reduces “software monoculture” (Chen et al , 2011; Temizkan et al , 2017; Biswas and Mukhopadhyay, 2018). Chen et al (2011) have developed a simulation-based study to identify the correlated risks arising due to shared software vulnerabilities across multiple software platforms.…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Qualitative research identified health information privacy concerns as barrier to wearable health technology growth (Becker 2018). While one would generally assume that these concerns impose greater threat to initial wearable adoption, research has demonstrated that data vulnerability grows over time as userbase increases (Biswas and Mukhopadhyay 2018). If software becomes more vulnerable to cyber-attacks over time, it might be a fruitful avenue for future research to assess the impact of privacy concerns on continuous smartwatch usage.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…For example the impact of trust in DAs was examined by Mihale-Wilson et al (2017). Further, these concerns can be external and internal: External, because digital assistants are software-based and hackers can exploit security vulnerabilities and access personal information (Biswas and Mukhopadhyay 2018). Internal, because DAs need a substantial amount of personal data for a meaningful personalization.…”
Section: Users' Privacy Perceptions and Privacy Assistancementioning
confidence: 99%